Etika dan Profesionalisme dalam Pembentukan Guru yang Berkarakter - Sulaiman Ahmad Zajuli; Astuti Darmiyanti (Peneliti.net, 2023)
The application of everyday competencies, pedagogic competencies, personality competencies, social competencies, and professional competencies are indications of professional educators with character. Students with character and quality can only be produced by professional teachers. Learning is an effective strategy for developing professional teachers with character. The purpose of this research is to identify teacher learning activities from planning to implementation and evaluation which are concrete evidence of their professionalism in utilizing pedagogic, professional, social, and personality competencies. The research and development process is based on the library research model. As a result, the teacher must instill his own character values ​​during this learning process in order to form students with character. Teachers can be role models for students apart from being educators and instructors